(untitled) (Medicine Today, 2018)
Pre-eclampsia is the most common medical complication of pregnancy associated with increased maternal and infant mortality and morbidity. Reduced serum calcium level are found associated with elevated blood pressure in preeclampsia. To evaluate serum calcium level in pre-eclamptic women. This cross sectional study was carried out in among 50 preeclamptic patients, aged 20 to 40 years, and gestational age ranges from 20 to 40 weeks and 50 age and gestational age matched normotensive pregnant women having no proteinuria. Serum calcium was measured by Colorimetric method. The mean age and mean gestational age of pre-eclampsia was not significantly different from those of normotensive pregnant women (p=0.203 and p=0.251 respectively). The mean body mass indexes of the test patients were significantly different from those of normotensive pregnant women (p<0.001). The mean serum calcium level was 7.27 ± 3.01 mg/dl in pre-eclampsia and 7.25 ± 2.59 mg/dl in normal pregnant women; did not differ significantly between the subjects of pre-eclampsia and normal pregnant women (p=0.963). Serum calcium has no association in occurrence of preeclampsia. Medicine Today 2018 Vol.30(2): 57-60